PREPARATION AND BASIC CHARACTERIZATION OF LIQUID SMOKE FROM EMPTY OIL PALM FRUIT BUNCHES (EFB): INITIAL QUALITY ASSESSMENT BEFORE REFINING - Seno Aji; Yakin Berdikari Waruwu; Suratni Afrianti (Agriprimatech, 2026)
Empty oil palm fruit bunches (EFB) are a solid waste from the palm oil industry that are produced in large quantities and have the potential to be converted into liquid smoke through a pyrolysis process. This study aims to produce liquid smoke from EFB and characterize its basic properties—including pH, total acid, phenolic content, yield, and color—as a reference for initial quality before the purification stage. The pyrolysis process was carried out at a temperature of 400°C for ±3 hours without further purification. The results showed that the liquid smoke produced was pitch black, stable without sediment after 7 days of storage at room temperature, with a pH value of 3.10, total acid of 2.08%, phenolic content of 15.61 ppm, and a yield of 2.97%. The low pH value indicates a high content of organic acids resulting from the degradation of lignocellulose components, while the dark black color indicates that the product still contains tar compounds, thus categorizing it as grade 3 liquid smoke. Compared with previous studies on similar raw materials, the total acid value and phenolic content in this study were relatively lower, which is thought to be related to differences in process conditions and the absence of a purification stage. OPEFB liquid smoke products have the potential to be developed as natural preservatives and botanical pesticides, but require further purification stages in the form of precipitation, filtration, and distillation to improve the quality to a higher grade before being applied on an industrial scale. Further research with analytical repetition, characterization of compound composition (GC-MS), and optimization of the purification process is recommended to strengthen the validity and applicability of the results.